Analisis Manajemen Penggunaan Dana Bank Berdasarkan Use of Fund by Priority dalam Mengoptimalkan Profitabilitas Perbankan Syariah di Indonesia - Nur Hasanah Bustam (ISLAMIC BUSINESS and FINANCE (IBF), 2021)
This study is to determine the effect Use of Funds by Priority in increasing the profitability of Islamic banking in Indonesia from 2011-2015. Samples in this study were 12 Islamic Banks and 22 Sharia Business Units. The data analysis method used is multiple linear regression analysis and hypothesis testing consisting of the F test, t-test, and R2 test. Based on the F test, it shows that simultaneously the variable placement of Wadhiah Demand Deposit funds with funds at BI, placement of funds in SWBI/SBIS, placement of funds in other Islamic banks, financing of mudharabah, financing of murabahah, and investment in securities has a significant effect on the profitability of Islamic banks in Indonesia. Meanwhile, partially with the t-test, it is found that the placement of Wadhiah Demand Deposit funds with BI, placement of funds with other Islamic banks, and investment in securities do not affect the profitability of Islamic banking in Indonesia. Meanwhile, the placement of funds in SWBI/SBIS and financing of mudharabah has a significant negative effect on the profitability of Islamic banking in Indonesia. Meanwhile, murabahah financing has a significant positive effect on the profitability of Islamic banking in Indonesia. Based on the R2 test, it was found that the contribution of the independent variable to the dependent variable was 68.9%, while the remaining 31.1% was influenced by other factors not included in this study.